Cosmology and eschatology in Hebrews : the settings of the sacrifice - Schenck, Kenneth L. (Cambridge [etc.] : Cambridge University Press, 2010)
"Scholars argue over where Hebrews fits in the first-century world. Kenneth L. Schenck works towards resolving this question by approaching Hebrews' cosmology and eschatology from a text-orientated perspective. After observing that the key passages in the background debate mostly relate to the 'settings ' of the story-of-salvation history evoked by Hebrews, Schenck attempts to delineate those settings by asking how the 'rhetorical world' of Hebrews engages that underlying narrative."--Jacket.
The quest for the historical Hebrews -- The rhetorical strategy of Hebrews -- The settings of the story in time -- The destiny of humanity -- The two ages -- The settings in space -- The spatial dualism of Hebrews -- The heavenly tabernacle in Hebrews.
Bibliography pages199-209 and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Biblical cosmology; Eschatology -- Biblical teaching